Evaluation of on growth and metabolism of NB-1691, an MYCN-amplified neuroblastoma cell line - Kaitlyn E Wong; Maria C Mora; Nazneen Sultana; Kevin P Moriarty; Richard B Arenas; Nagendra Yadava; Sallie S Schneider; Michael V Tirabassi (Tumor Biology, 2018)
Outcomes of children with high grade neuroblastoma remain poor despite multi-agent chemotherapy regimens. Rhodiola crenulata extracts display anti-neoplastic properties against several cancers including breast cancer, melanoma, and glioblastoma. In this study, we evaluated the anti-neoplastic potential of Rhodiola crenulata extracts on human neuroblastoma cells. Through this work, cell viability and proliferation were evaluated following treatments with ethanol (vehicle control) or Rhodiola crenulata extract in neuroblastoma, NB-1691 or SK-N-AS cells, in vitro . HIF-1 transcriptional activity was evaluated using a dual luciferase assay. Quantitative real-time polymerase chain reaction was utilized to assess the expression of HIF-1 targets. Selected metabolic intermediates were evaluated for their ability to rescue cells from Rhodiola crenulata extract-induced death. Lactate dehydrogenase, pyruvate kinase, and pyruvate dehydrogenase activities and NAD + /NADH levels were assayed in vehicle and Rhodiola crenulata extract-treated cells. The effects of Rhodiola crenulata extracts on metabolism were assessed by respirometry and metabolic phenotyping/fingerprinting. Our results revealed striking cytotoxic effects upon Rhodiola crenulata extract treatment, especially prominent in NB-1691 cells. As a greater response was observed in NB-1691 cells therefore it was used for remaining experiments. Upon Rhodiola crenulata extract treatment, HIF-1 transcriptional activity was increased. This increase in activity correlated with changes in HIF-1 targets involved in cellular metabolism. Serendipitously, we observed that addition of pyruvate protected against the cytotoxic effects of Rhodiola crenulata extracts. Therefore, we focused on the metabolic effects of Rhodiola crenulata extracts on NB-1691 cells. We observed that while the activities of pyruvate kinase and pyruvate dehydrogenase activities were increased, the activity of lactate dehydrogenase activity was decreased upon Rhodiola crenulata extract treatment. We also noted a decline in the total NAD pool following Rhodiola crenulata extract treatment. This correlated with decreased cellular respiration and suppressed utilization of carbon substrates. Through this work, we observed significant cytotoxic effects of Rhodiola crenulata extract treatment upon treatment on NB-1691 cells, a human neuroblastoma cell line with MYCN amplification. Our studies suggest that these cytotoxic effects could be secondary to metabolic effect induced by treatment with Rhodiola crenulata extract.